UJI TOKSISITAS AKUT EKSTRAK ETANOL 70% DAUN HULOTUA (Commelina Longifolia L.) SECARA IN VITRO DENGAN METODE Brine Shrimp Lethality Test (BSLT) - Suryadi, A. Muthi Andi; Pakaya, Mahdalena Sy.; Taupik, Muhammad; Uno, Wiwit Zuriati; Manno, Mohamad Reski; kopman, aldafarista (Journal of Pharmacology and Natural Products, 2024)
All chemical substances classified as drugs must undergo evaluation for their toxicological qualities prior to widespread acceptance in traditional medicine by the community. The Brine Shrimp Lethality Test (BSLT) method is a preliminary test using shrimp larvae to observe the toxic effects of a compound in plant extracts. This study aimed to determine the toxicity of 70% ethanol extract of Hulotua (Commelia longifolia L.) leaves in vitro using the Brine Shrimp Lethality Test (BSLT) method. This study employed an experimental method through phytochemical screening using a color test and toxicity testing using Brine Shrimp Lethality Test (BSLT) method. The results of phytochemical screening using the tube test method indicated that 70% ethanol extract was positive for alkaloids, flavonoids, tannins and terpenoids. In the meantime, an acute toxicity test of 70% ethanol extract of Hulotua ( Commelia longifolia L.) leaves was slightly toxic to Artemia salina larvae where the LC50 value >1000 µg/mL was 670.049 µg/mL.